Active noise control for construction noise - Neo, Ling Pin (Nanyang Technological University, 2023)
This project aims to design the power supply boxes of an active noise control system for construction noise. The effectiveness of the active noise control system is also evaluated in the paper using the preliminary measurements that were collected.